Human induced conservation in the natural islets. Status of vertebrate diversity in the selected sacred forests of Kerala India - Pazhedath Vasudevan, Krishnanand; Karumampoyil Sakthidas, Dr. K S Anoop Das (Acta Geographica Debrecina Landscape & Environment series, 2025)
Sacred forests are conserved based on religious aspects. Regional differences are visible among sacred groves in their management policies, temple construction, landscapes, and religious beliefs. This study analyzed whether there is any relationship between vertebrate species diversity and the management policies adopted by respective owners. To examine this, twenty sacred groves were selected. The vertebrates, such as birds, reptiles, amphibians, and mammals were surveyed, which lasted up to 2 years. Specific methodologies, such as point count for bird survey and visual encounter surveys for other vertebrates, were followed. To analyze the management policies adopted by the respective owners, nine parameters were considered, and each parameter was given a score for all the study sites. 135 species of vertebrates were recorded, and their species diversity is estimated by using the Shannon Wiener Index. To estimate the association between the management policies and species diversity, the scores of each parameter for all the sacred groves were summed and correlated with the Shannon‒Wiener index. A positive correlation between these factors obtained indicated that the management policies taken by the owners influenced the species conservation.